Risk factors and clinical management of haemorrhage after open nephron-sparing surgery - Huber, Johannes; Pahernik, Sascha; Hallscheidt, Peter; Sommer, Christof-Matthias; Hatiboglu, Gencay; Haferkamp, Axel; Hohenfellner, Markus (BJU international, 2010)
Study Type - Therapy (case series) Level of Evidence 4 OBJECTIVE To identify risk factors for relevant haemorrhage after open nephron-sparing surgery (NSS) for renal cell carcinoma, and to evaluate its clinical management. PATIENTS AND METHODS We evaluated bleeding complications after open NSS in 196 consecutive cases (193 patients) at our institution. The median (range) age of the patients was 64 (3-91) years and the tumour diameter was 2.7 (0.5-11.8) cm. Sex, age, body mass index, imperative vs elective indication, year of surgery, multifocality, tumour diameter and malignant vs benign pathology were tested exploratively and significant variables entered in a multivariate model. The clinical management of haemorrhage after NSS was analysed. RESULTS Bleeding required conservative (six), interventional (six) or surgical (three) therapy in 15 of the 196 cases (8%). Imperative indication (P= 0.043) and multifocality (P= 0.039) were independent risk factors in a multivariate model. Compared with superselective percutaneous transarterial embolization (TAE), surgery as a primary therapeutic option was more likely within 24 h after NSS (P= 0.012). Bleeding was finally controlled in all patients, while the kidney was preserved in 11 patients. There was only a minor decline of renal function at the 3-month follow-up. CONCLUSIONS We identified multifocal tumours and imperative indication as risk factors for haemorrhage after NSS. The management was very successful, relying on TAE as an effective and safe treatment for bleeding after NSS. In rare cases of severe bleeding surgical exploration is unavoidable, with a lower chance of kidney preservation.